2010
DOI: 10.1007/s12011-010-8750-x
|View full text |Cite
|
Sign up to set email alerts
|

Status of Copper and Magnesium Levels in Diabetic Nephropathy Cases: a Case-Control Study from South India

Abstract: Diabetic nephropathy is a complication of diabetes mellitus. This present study investigates the status of copper and magnesium in diabetic nephropathy cases to establish a possible relation. Forty patients of diabetic nephropathy participated in the study as cases. Forty age- and sex-matched healthy individuals served as controls. Blood samples were collected from both cases and controls for determination of FBS, PPBS, HbA1c, microalbumin, copper, and magnesium levels. The mean concentrations of FBS, PPBS, Hb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
1
13
1
1
Order By: Relevance
“…Without the results of serum copper as a confounding factor, the interpretation of the results of our study is difficult, although Prabodh in a study from India did not find significant difference of serum copper between diabetic patient with and without nephropathy. [10] Also, some animal and human studies have evaluated serum or urine ceruloplasmin to better clarify the roles of copper in similar settings. [121517] However, multiple other studies have evaluated serum or urinary copper without concurrent evaluation of ceruloplasmin.…”
Section: Discussionmentioning
confidence: 99%
“…Without the results of serum copper as a confounding factor, the interpretation of the results of our study is difficult, although Prabodh in a study from India did not find significant difference of serum copper between diabetic patient with and without nephropathy. [10] Also, some animal and human studies have evaluated serum or urine ceruloplasmin to better clarify the roles of copper in similar settings. [121517] However, multiple other studies have evaluated serum or urinary copper without concurrent evaluation of ceruloplasmin.…”
Section: Discussionmentioning
confidence: 99%
“…Hypomagnesemia has been implicated in the development of diabetic complications due to enhanced renal Mg excretion [6,13,14]. The study of Prabodh suggested that hypomagnesemia may be related to development of diabetic nephropathy [15]. Hypomagnesemia was found to be related to weak glycemic control and increased incidence of nephropathy and retinopathy [16].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium is an important cofactor in several key enzymes involved in carbohydrate metabolism and is considered to play a role in glucose homeostasis and insulin action (11,12). Zinc is essential for the formation of both the stored and active forms of insulin and may be involved in the development or progression of both type 1 and type 2 diabetes (13)(14)(15). Copper and iron play important roles in the pathological processes that are ongoing in diabetic patients by participating in free radical reactions (16).…”
Section: Popular Scientific Summarymentioning
confidence: 99%